Natural food flavors and colorants - Attokaran, Mathew (IFT Press series, 2011)
"Natural Extracts as Food Flavors and Colorants, as its name implies, describes the natural extracts that are used as food flavors and colors. Part I addresses techniques and general characteristics of these natural extracts, including essential oils; solvent extraction; food colors; dispersion and solubitization; effect of heat; nutraceutical function; organoleptic function; and regulatory and analytical aspects. Part II focuses on each individual natural extract, with coverage including raw material; chemistry; extraction specifics; methods of testing; and uses. Chemical structure and properties of key constituents are provided. Wherever available, CAS number, FEMA number and E number are given. Determination of principal and significant constituents is described, so as to help analysts choose the right methods. Food scientists, researchers and product development professionals alike will find Natural Extracts as Food Flavors and Colorants an invaluable resource for understanding and using these natural food ingredients"--Provided by publisher.